Structural Distortion of Cycloalkynes Influences Cycloaddition Rates both by Strain and Interaction Energies - Hamlin, Trevor A. (Chemistry, 2019)
The reactivities of 2‐butyne, cycloheptyne, cyclooctyne, and cyclononyne in the 1,3‐dipolar cycloaddition reaction with methyl azide were evaluated through DFT calculations at the M06‐2X/6‐311++G(d)//M06‐2X/6‐31+G(d) level of theory. Computed activation free energies for the cycloadditions of cycloalkynes are 16.5–22.0 kcal mol(−1) lower in energy than that of the acyclic 2‐butyne. The strained or predistorted nature of cycloalkynes is often solely used to rationalize this significant rate enhancement. Our distortion/interaction–activation strain analysis has been revealed that the degree of geometrical predistortion of the cycloalkyne ground‐state geometries acts to enhance reactivity compared with that of acyclic alkynes through three distinct mechanisms, not only due to (i) a reduced strain or distortion energy, but also to (ii) a smaller HOMO–LUMO gap, and (iii) an enhanced orbital overlap, which both contribute to more stabilizing orbital interactions.